Isolation and translation of mRNA coding for the variant surface antigens of Paramecium. - Sommerville, J (1983)
In the poly(A)+RNA isolated from the ciliate Paramecium primaurelia is found a discrete and abundant mRNA species of high molecular weight (corresponding to about 9,000 nucleotides). This mRNA species has size and abundance characteristics that identify it tentatively as the message coding for the variant cell-surface antigens. After microinjection of the high molecular weight mRNA into amphibian oocytes, polypeptides are synthesized that are immunoprecipitated specifically with antibodies directed against the homologous Paramecium antigen. On collecting the culture medium of oocytes microinjected with Paramecium mRNA, newly-synthesized complete antigen molecules (Mr approximately 300,000) can be recovered by immunoprecipitation.